Pengembangan Media Pembelajaran Interaktif Berbasis Quizalize pada Mata Pelajaran Otomatisasi Tata Kelola Kepegawaian di SMK - Monika Simare Mare; Henry Eryanto; Roni Faslah (Syntax Corporation Indonesia, 2024)
The aim of this research is to develop interactive learning media based on Quizalize in civil service OTKP subjects and to find out the feasibility of interactive learning media based on Quizalize in Civil Service OTKP subjects for Karya Teladan Vocational School students. This type of research uses the ADDIE development method, namely Analysis, Design, Development, Implementation and Evaluation. This research took place at Karya Teladan Vocational School and was conducted in May 2024. Data was collected by means of assessments by media experts and material experts. Based on research that has been carried out and developed by validation experts, it is known that Quizalize-based interactive learning media for the OTKP Civil Service subject for Karya Teladan Vocational School students is very suitable for use. The average result for media experts was 90.43% and material experts 95.23, so it was categorized as